Improving substructure works safety performance rating using six sigma methodology - Theayavalan, Vasudevan (2022)
the occupational accident rate is one of the highest across all other industrial sectors. Low safety performance can possibly contribute to occupational accident. The Solaris 1 construction project site monthly safety performance ratings were below the target 70% set by the client. This research used the Six Sigma DMAIC process framework to improve the monthly safety performance and maintain the score rating of above 70% until the end of the construction project. The research indicated that safety leadership plays a significant role in enhancing workplace safety performance. This paper attempts to provide a conceptualization of safety leadership from the perspective of Malaysia’s construction sector. It was proposed that positive safety leadership leads to an increase of construction safety performance. It was proposed that positive safety leadership leads to an increase of construction safety performance. Safety leadership of two senior managements, three managers and seven supervisors at Solaris 1 construction site were examined and improved. Using Six Sigma DMAIC methodology, positive safety leadership was established and safety performance rating improved above 70% from March 2019 onwards. Safety leadership acts an important role in determining the level of workplace safety through safety coaching, safety caring, and safety controlling. Furthermore, the perception of employees towards safety-related leadership in the organizations influences their behaviour in handling their works. This suggests that the Six Sigma DMAIC methodology and analysis tool can be easily adopted to improve safety performance at construction site.